Multimedia : a management perspective - Alber, Antone F. (Integrated Media Group, 1996)
This book is divided into five sections: Setting the Stage; Dancing Cars and Talking Teacups; The Building Blocks; Storing, Compressing, and Transmitting; Multimedia in Action.